Silicon dioxide atomic layer deposition at low temperature for PDMS microlenses coating - Cunha, Florival Moura (2024)
The optical performance of a microlens is strongly affected by its surface roughness, which depends on its fabrication process. High-surface roughness leads to scattering issues, decreasing the optical efficiency of a microlens. In this work, a polydimethylsiloxane microlens was coated with a very thin-film of silicon dioxide (30 nm), deposited by plasma-enhanced atomic layer deposition at a low temperature (50 °C). The main goal was to passivate the polymeric microlens and reduce its surface roughness. Atomic force microscopy was performed before and after the silicon dioxide coating, confirming the surface roughness reduction by a factor of 3.2. The microlens was observed by scanning electron microscopy after silicon dioxide coating. Surface elemental composition analysis of the silicon dioxide thin-film was also performed through X-ray photoelectron spectroscopy, confirming the formation of silicon dioxide and a stoichiometric ratio of silicon to oxygen (Si:O) close to 27:58. The refractive index of the deposited film was measured by ellipsometry, obtaining a value of 1.4617 at 470 nm.